Conversing with Lawrence C. Heilman’s USAID in Bolivia: Partner or Patrón? - Chris Krueger (Bolivian Studies Journal, 2018)
This piece works off the contents of Larry Heilman´s book also based largely on his personal experience of decades in USAID and subsequent research over at least ten years. The first part follows the chronology of his work, that covers some 70 years of U.S. development assistance to Bolivia citing key points for each period. A second part provides information about the view of development/wellbeing in today’s Bolivia. Finally, some elements are presented to consider a possible new era of cooperation beyond the current impasse.